2020
DOI: 10.1016/j.isci.2020.101732
|View full text |Cite
|
Sign up to set email alerts
|

Individuals Prioritize the Reach Straightness and Hand Jerk of a Shared Avatar over Their Own

Abstract: Summary Cyber space enables us to “share” bodies whose movements are a consequence of movements by several individuals. But whether and how our motor behavior is affected during body sharing remains unclear. Here we examined this issue in arm reaching performed by a shared avatar, whose movement was generated by averaging the movements of two participants. We observed that participants exhibited improved reaction times with a shared avatar than alone. Moreover, the reach trajectory of the shared ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The representation of our body in the brain is plastic. Even relatively short multi-sensory (usually visuo-haptic) stimulations can induce an illusion of ownership, and embodiment in general, towards artificial limbs and bodies 1 including human-looking limbs: rubber hands 2 , 3 , virtual avatars 4 6 , as well as robotic limbs and bodies 7 14 . However, most previous studies on ownership have been conducted in the context of “limb substitution,” where the rubber, virtual, or robotic limb replaces an already-existing limb.…”
Section: Introductionmentioning
confidence: 99%
“…The representation of our body in the brain is plastic. Even relatively short multi-sensory (usually visuo-haptic) stimulations can induce an illusion of ownership, and embodiment in general, towards artificial limbs and bodies 1 including human-looking limbs: rubber hands 2 , 3 , virtual avatars 4 6 , as well as robotic limbs and bodies 7 14 . However, most previous studies on ownership have been conducted in the context of “limb substitution,” where the rubber, virtual, or robotic limb replaces an already-existing limb.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we explore a new concept called “virtual co-embodiment” where two or more users embody one avatar to collaboratively perform joint tasks. Co-embodiment can be achieved in several ways such as reflecting average movements (or movements in different ratios of control) of multiple users to one avatar/robot 7 , 8 , allowing multiple users to control different sections of one avatar limb/robotic arm 9 , and allowing each user to fully control separate limbs of one avatar 10 , 11 . We are focusing on this third method; We utilized an avatar of which left and right limbs could be controlled by two different individuals at the same time while both of them were immersed in the first-person view of the virtual avatar.…”
Section: Introductionmentioning
confidence: 99%
“…1 A). Hagiwara et al 8 conducted an experiment where two human participants were embodied within a concurrent shared avatar (Fig. 1 A) in VR and showed that the movements of the shared avatar were straighter, and less jerky compared to the movements of the individual participants and the solo body avatar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The representation of our body in the brain is plastic. Even relatively short multi-sensory (usually visuo-haptic) stimulations can induce an illusion of ownership, and embodiment in general, towards artificial limbs and bodies (Aymerich-Franch and Ganesh, 2016) including human-looking limbs: rubber hands (Botvinick and Cohen, 1998;Longo et al, 2008), virtual avatars (Slater et al, 2009(Slater et al, , 2010Hagiwara et al, 2020) as well as robotic limbs and bodies (Nishio et al, 2012;Alimardani et al, 2013;Suzuki et al, 2015). However, most previous studies on ownership have been conducted in the context of 'limb substitution,' where the rubber, virtual or robot limb replaces an already-existing limb.…”
Section: Introductionmentioning
confidence: 99%